Food availability aligns with contrasting demographics in populations of an at‐risk songbird - Emma C. Keele; Cameron J. Fiss; Darin J. McNeil; Meredith Anderson; Nathan Thomas; Dakotah Shaffer; Jeffery L. Larkin (Ecology and Evolution)
Abstract Golden‐winged Warblers (Vermivora chrysoptera) have become rare across much of their historic breeding range and response to conservation efforts is variable. Evidence from several recent studies suggests that breeding output is a primary driver explaining responses to conservation and it is hypothesized that differences in food availability may be driving breeding output disparity between two subpopulations of the warbler's Appalachian breeding range. Herein, we studied two subpopulations: central Pennsylvania (“central subpopulation”), where breeding productivity is relatively low, and eastern Pennsylvania (“eastern subpopulation”), where breeding productivity is relatively high. To test the food‐availability hypothesis in this system, we measured density of caterpillars, plasma lipid metabolites (triglycerides [TRIG; fat deposition] and glycerol [GLYC; fat breakdown]), body mass of adults males, and acquired body mass data for fledglings at 38 sites managed for nesting habitat. Consistent with our prediction, leaf‐roller caterpillar density, the group upon which Golden‐winged Warblers specialize, was 45× lower in the central subpopulation than the eastern subpopulation. TRIG concentrations were highest within the eastern subpopulation during breeding grounds arrival. The change in TRIG concentrations from the breeding‐grounds‐arrival stage to the nestling‐rearing stage was subpopulation dependent: TRIG decreased in the eastern subpopulation and was constant in the central subpopulation, resulting in similar concentrations during the nestling‐rearing stage. Furthermore, GLYC concentrations were higher in the eastern subpopulation, which suggests greater energy demands in this region. Despite this, adult male warblers in the eastern subpopulation maintained a higher average body mass. Finally, fledgling body mass was 16% greater in the eastern subpopulation than the central subpopulation before and after fledging. Collectively, our results suggest that poor breeding success of Golden‐winged Warblers in the central subpopulation could be driven by lower availability of primary prey during the breeding season (leaf‐roller caterpillars), and this, in turn, limits their response to conservation efforts.